Metagenomics and metabolomics integrated to explore the protective mechanisms of Mongolian medicine Zadi-5 in myocardial ischemic model rats - Wu, Riga; Zu, Wen; Wei, Lisi; Wu, Rihan; Su, Si; A, Ruhan; A, Tengarile; E, Nirile; Li, Hua; Hu, Rilebagen; Li, Li (Frontiers in Microbiology, 2026)
BackgroundMyocardial ischemia (MI) is a pathological state of abnormal energy metabolism caused by insufficient blood and oxygen supply to the coronary arteries. The “gut-heart axis” theory plays an important role in myocardial ischemia occurrence, mechanism, prevention, and cure. Traditional Mongolian medicine posits that “internal diseases originate from gastrointestinal dysfunction,” linking the intestine, a key component of the digestive system, to physiological and pathological changes in the heart. Furthermore, the traditional Mongolian clinical treatment of cardiovascular diseases includes guidelines for digestive system function corresponding to the modern concept of the gut-heart axis. Accordingly, Zadi-5, a traditional Mongolian medicine, has been used for over 200 years to prevent and treat cardiovascular diseases. However, the mechanism by which the gut microbiota and metabolism are regulated to protect an ischemic heart is unclear.AimThis study aimed to investigate the potential mechanism by which Zadi-5, through its interaction with the gut microbiota and metabolic pathways, alleviates myocardial ischemic injury induced by a high-fat diet and isoproterenol (ISO).MethodsSprague-Dawley rats were divided into control, model, Zadi-5 high-dose, and Zadi-5 low-dose groups. All groups, except the control group, were fed a high-fat diet for 4 weeks. Subsequently, all animals received subcutaneous injections of 4 mg/kg ISO daily for 3 days to induce a myocardial infarction (MI) rat model. The pharmacological effects of Zadi-5 on MI were assessed using electrocardiography (ECG), hematoxylin-eosin (HE) staining of myocardial tissue, and serum levels of cardiac troponin T (cTn-T), creatine kinase-MB (CK-MB), lactate dehydrogenase (LDH), total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C). Furthermore, fecal metagenomics and serum untargeted metabolomics were performed to investigate the protective mechanisms of Zadi-5 against MI. Finally, MetOrigin was used to analyze the correlation between key metabolic pathways and the gut microbiota to elucidate the mechanism by which Zadi-5 protects against myocardial ischemia.ResultsFirst, the MI rat model was successfully established by ISO, and Zadi-5 significantly preserved MI injury, according to ECG recording, index of TC, TG, LDL-C, cTn-T, LDH, CK-MB, and histopathology results. Second, Zadi-5 regulates gut microbiota diversity and abundance, as well as glutamine and glutamate metabolism. The mechanism is related to the gut microbiota phyla Actinobacteria, Firmicutes, Bacteroidetes, and Proteobacteroidetes, and classes Gammaproteobacteria, Betaproteobacteria, Bacteroidia, Actinomycetes, Clostridia, and Bacilli. Zadi-5 also regulates L-glutamic acid, L-glutamine, ornithine, and oxaceprol metabolisms.ConclusionZadi-5 exerts cardioprotective effects in MI rats by improving dysbiosis of the gut microbiota and regulating the glutamate–glutamine metabolism pathway. This may represent only one of the complicated protective mechanisms of Zadi-5 against MI. The cardioprotective mechanisms of Zadi-5 will be explored at the molecular and cellular levels.